Cash-in-the-Market Pricing and Optimal Resolution of Bank Failures - Acharya, Viral V.; Yorulmazer, Tanju (Review of Financial Studies, 2008)
Regulation Conference at the Bank of Portugal, and two anonymous referees for useful comments. All errors remain our own.